Princípios formais e discricionariedade do legislador tributário: limites ao estorno de crédito de ICMS em isenções concedidas em etapas intermediárias da cadeia produtiva - Dantas, Eric de Moraes e (2023)
The boundaries of tax legislative activity, considered as the starting point of the present study, are closely linked to the theoretical framework of fundamental rights. In this investigation, we sought identify methodological aspects of this conception through the application of formal principles model to this activity, particularly regarding the limits to the extrafiscal tax legislator, especially when exercising the specific competence of the extra-fiscal legislator of the Tax on Circulation of Goods and Services (ICMS, abbreviation in Portuguese) to deal with the use or not of the credits from previous stages of the production chain of goods or service. The formal principles, within the scope of this research, are seen as procedural norms that subsidize and direct the application of norms with material content, such as fundamental rights. Based on this premise, we sought to determine the existence or absence of a necessary correlation between the formal principle of the ICMS legislator‟s competence to address the reversal of credits in the exemptions granted at intermediate stages of the production chain, when granted with the intention of optimizing fundamental rights that are not related strictly to taxation, non-cumulativeness, constitutional limitations on tax legislator, and those granted to taxpayers. The result of such investigation came with the verification that, in the exercise of extra-fiscal competence, not all limitations on tax legislator are manifestations of a legal good endowed with jusfundamentality or that neither revert themselves, necessarily, in favor of the taxpayer either. The theoretical ballast invoked to structure this conception does not remove – in fact, it complements and supports – its analytical confrontation in the face of the positivized norms in the Constitution of the Federative Republic of Brazil of 1988. It would be intuitive, therefore, to consider that the central point of the research object is the dogmatic surrounding fundamental rights, notably with regard to its facet of study as to the material principles. However, what was sought was to elucidate from another perspective and to approach only peripherally. Consequently, the conceptual onlending of the correlated legal institutes was essential, such as: the scope of protection; the factual support; the conformation; the restriction; the configuration; the freedom of conformation of the legislator; the discretion of the legislator; among others. The respective topics of the research were formulated inseparably from the defining parameters of what is called “discretion of the legislator,” taking into account its association with the normative burden of fundamental rights and with the formal principles. Moreover, the perspective of a rational methodology capable of justifying its compatibility with the precepts contained in the constitutional text was considered indispensable, considering that its theoretical postulations originate, to a large extent, from foreign legal literature.